Determinants of preterm birth at Jimma University Medical Center, southwest Ethiopia - Abaraya M; Seid SS; Ibro SA (Dove Medical Press, 2018)
Mohammed Abaraya,1 Sheka Shemsi Seid,2 Shemsedin Amme Ibro2 1Jimma University Medical Center, Jimma University, Jimma, Ethiopia; 2School of Nursing and Midwifery, Jimma University, Jimma, Ethiopia Background: Preterm birth is the second leading cause of death next to pneumonia in children aged <5 years and the single-most important cause of death in the first month of life. Research examining determinants of preterm birth in Ethiopia is limited. Therefore, this study aimed to determine risk factors associated with preterm births at Jimma University Medical Center in southwest Ethiopia. Methods: This unmatched case–control study was conducted from March 15 to April 1, 2017 from medical records of mothers and newborns delivered at Jimma University Medical Center from January 1 to December 30, 2016. Data were extracted using a structured checklist for cases (preterm) and controls (term) by reviewing maternal and newborn medical records using a simple random-sampling technique. Risk factors for preterm delivery were determined using bivariate and multivariate logistic regression models. Statistically significant associations were declared at P<0.05. Results: The present study evaluated 218 maternal and newborn cases and 438 controls. Risk factors identified were history of previous preterm birth (AOR 6.4, 95% CI 2.9–13.9), preeclampsia (AOR 6.6, 95% CI 3.3–13.4), premature membrane rupture (AOR 11.7, 95% CI 6.2–21.9), antenatal care of fewer than four visits (AOR 4.8, 95% CI 1.2–19), birth interval <2 years (AOR 2.7, 95% CI 1.7–4.5), and multiple pregnancies (AOR 4.5, 95% CI 2.4–8.5). Conclusion: History of previous preterm births, preeclampsia, premature membrane rapture, antenatal care of fewer than four visits, birth interval <2 years, and multiple pregnancies were found to have a possible causal relationship with preterm births. Therefore, similar further studies should be conducted to generate more population-based evidence on determinants of preterm births. Keywords: determinants, preterm birth, pregnant women, gestational age, newborn